El portesgilismo en Tamaulipas : estudio sobre la constitución de la autoridad pública en el México posrevolucionario - Alvarado Mendoza, Arturo (Book collections on Project MUSE., 1992)
"Detailed analysis of the political activities of Emilio Portes Gil in his native state during the 1920s. Demonstrates the extent to which Mexico's post-revolutionary political system (based on corporatism and presidentialism) was a product of the local consolidation of power"--Handbook of Latin American Studies, v. 58.